2016
DOI: 10.1007/s00192-016-3238-7
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic organ prolapse: prevalence and risk factors in a Brazilian population

Abstract: We found that a majority of the population sample exhibited some degree of prolapse, suggesting that POP deserves substantial clinical attention. The risk factors identified suggest that eventual prolapse may be unavoidable in some women. Public policies should be implemented with respect to modifiable risk factors and antenatal care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
1
8

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 27 publications
0
30
1
8
Order By: Relevance
“…Nurses with more severe symptoms were obese and had lower job satisfaction and more intention to leave their current job (P < .001) it is well documented that these disorders do not take place in isolation. 1,3,8,9 Furthermore, PFD affects wo-menʼs QoL, with significant increases in depression, embarrassment, and social isolation, as highlighted in the selected studies, with the impact on different aspects of life contributing to the growing socioeconomic and health problems of PFD for society. 8,28 Therefore, PFD, either alone or combined, has been studied in specific populations that present greater risk, such as women, older adults, and nursing staff.…”
Section: Iciqui-sfmentioning
confidence: 99%
See 1 more Smart Citation
“…Nurses with more severe symptoms were obese and had lower job satisfaction and more intention to leave their current job (P < .001) it is well documented that these disorders do not take place in isolation. 1,3,8,9 Furthermore, PFD affects wo-menʼs QoL, with significant increases in depression, embarrassment, and social isolation, as highlighted in the selected studies, with the impact on different aspects of life contributing to the growing socioeconomic and health problems of PFD for society. 8,28 Therefore, PFD, either alone or combined, has been studied in specific populations that present greater risk, such as women, older adults, and nursing staff.…”
Section: Iciqui-sfmentioning
confidence: 99%
“…Female pelvic floor dysfunctions (PFDs) and lower urinary tract symptoms (LUTSs) include a variety of symptoms, such as urinary incontinence (UI), stress urinary incontinence (SUI), urge urinary incontinence (UUI), and mixed urinary incontinence (MUI). 1,2 Other LUTSs include bladder storage, voiding, and postmicturition symptoms, 1,3 while female PFDs incorporate pelvic organ prolapse (POP) and sexual and anorectal dysfunction symptoms, including anal incontinence and constipation. 1,2 Pelvic floor dysfunctions and LUTS are important public health issues due to their high prevalence.…”
Section: Introductionmentioning
confidence: 99%
“…Prevalence of symptom base POP among Emirati women estimated 26.9% by Elbis et al [13]. While Horst et al [14] showed that prevalence of POP with using of pelvic organ prolapse quantification (POP-Q) measurement system is more than 50%. Due to different prevalence and risk factors extracted from different studies, the present study aimed to assessment prevalence and defining risk factor of UI/AI as well as POP among healthy postmenopausal women.…”
Section: Introductionmentioning
confidence: 99%
“…Another differential diagnosis is pelvic organ prolapses (POP), which is a "herniated vagina" containing one pelvic organ (bladder, rectum, or uterus) [12]. Although the urinary symptoms in the POPs are similar to the prolapsed ureterocele, such as sensation of heaviness in the pelvis, urinary urgency or frequency, voiding dysfunction, and others [13], we can distinguish from prolapsed ureterocele observing the prolapse from the vagina, not from the urethra, through pelvic examination with a Sims' speculum or a bivalve speculum [13].…”
Section: Discussionmentioning
confidence: 99%